ANALYSIS OF INTERNAL CONTROL AND FRAUD : A CASE STUDY ON GARUDA INDONESIA - Meiryani Meiryani; Aisyah Aulia Primado (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2023)
The research in this paper is to report that PT Garuda Indonesia's financial statements in 2018 experienced fraud in accordance with the news circulating. The object in this paper's research is the financial statements of PT Garuda Indonesia which is suspected of fraud. Researchers use qualitative analysis methods based on looking at data in related sources. So, it can be concluded that Garuda Indonesia may be wrong to implement PSAK in accordance with the rules on its financial statements. This paper also attaches sanctions imposed on PT Garuda Indonesia as well as what internal controls are carried out by PT Garuda on the case.